2023
DOI: 10.1136/jmg-2023-109269
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical implications of germline pathogenic variants in cancer predisposing genes in young patients across sarcoma subtypes

Abstract: BackgroundSarcomas are a rare and diverse group of cancers occurring mainly in young individuals for which an underlying germline genetic cause remains unclear in most cases.MethodsGermline DNA from 177 children, adolescents and young adults with soft tissue or bone sarcomas was tested using multigene panels with 113 or 126 cancer predisposing genes (CPGs) to describe the prevalence of germline pathogenic/likely pathogenic variants (GPVs). Subsequent testing of a subset of tumours for loss of heterozygosity (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
2
0
0
Order By: Relevance
“…Similarly, we observed more P/LP in patients with family history for malignancy, but the difference was not statistically significant. This conclusion is parallel to Carvalho et al, who demonstrated higher mutation rates in patients with positive family history, although this was not statistically significant either [55].…”
Section: Discussionsupporting
confidence: 81%
“…Similarly, we observed more P/LP in patients with family history for malignancy, but the difference was not statistically significant. This conclusion is parallel to Carvalho et al, who demonstrated higher mutation rates in patients with positive family history, although this was not statistically significant either [55].…”
Section: Discussionsupporting
confidence: 81%
“…We add to a body of evidence demonstrating the clinical value of CMP beyond the ability to identify new treatment options [23,24]. Of major importance to AYA patients, CMP led to the identification of pathogenic germline variants in 12% of our cohort, which is similar to previous reports in this population [25,26], although this is notably less than the finding of 55% in a large multisite cohort of 1162 adult sarcoma patients [27]. Our department now advocates for referral to a familial cancer centre to offer germline testing for all patients under 40 years with sarcoma, as well as for older patients with a suggestive personal or family history.…”
Section: Discussionsupporting
confidence: 80%